Comparative Study of Different Sampling Methods of Biofilm Formed on Stainless-Steel Surfaces in a CDC Biofilm Reactor - Niboucha, Nissa; Goetz, Coralie; Sanschagrin, Laurie; Fontenille, Juliette; Fliss, Ismaïl; Labrie, Steve; Jean, Julie (Frontiers in Microbiology, 2022)
The formation of biofilms in dairy processing plants can reduce equipment efficiency, contribute to surface deterioration, and contaminate dairy products by releasing the microorganisms they contain, which may cause spoilage or disease. However, a more representative identification of microbial communities and physico-chemical characterization requires to detach and recover adequately the entire biofilm from the surface. The aim of this study is to develop an efficient technique for in-plant biofilm sampling by growing a strain of Pseudomonas azotoformans PFl1A on stainless-steel surface in a dynamic CDC biofilm reactor system using tryptic soy broth (TSB) and milk as growth media. Different techniques, namely, swabbing, scraping, sonic brushing, synthetic sponge, and sonicating synthetic sponge were used and the results were compared to a standard ASTM International method using ultrasonication. Their efficiencies were evaluated by cells enumeration and scanning electron microscopy. The maximum total viable counts of 8.65 ± 0.06, 8.75 ± 0.08 and 8.71 ± 0.09 log CFU/cm2 were obtained in TSB medium using scraping, synthetic sponge, and sonicating synthetic sponge, respectively, which showed no statistically significant differences with the standard method, ultrasonication (8.74 ± 0.02 log CFU/cm2). However, a significantly (p < 0.05) lower cell recovery of 8.57 ± 0.10 and 8.60 ± 0,00 log CFU/cm2 compared to ultrasonication were achieved for swabbing and sonic brushing, respectively. Furthermore, scanning electron microscopy showed an effective removal of biofilms by sonic brushing, synthetic sponge, and sonicating synthetic sponge; However, only the latter two methods guaranteed a superior release of bacterial biofilm into suspension. Nevertheless, a combination of sonication and synthetic sponge ensured dislodging of sessile cells from surface crevices. The results suggest that a sonicating synthetic sponge could be a promising method for biofilm recovery in processing plants, which can be practically used in the dairy industries as an alternative to ultrasonication.